Application of the Dangerous Preparation Directive: consequences on plant protection products in the internal market - Maristella Rubbiani; Laura Fornarelli; Susanna Bascherini; Roberto Binetti (Istituto Superiore di Sanità, 2010)
Legislative Decree March 2003, n. 65 brought about implementation of Directive 1999/45/ EC of the European Parliament and of the Council dated 31 May 1999 and Directive 2001/60/EC of the Commission dated 7 August 2001 concerning laws, regulations and administrative provisions of the Member States relating to the classification, packaging and labelling of dangerous preparations come into force. Directive 1999/45/EC brought about a series of modifications representing the new regulatory framework for dangerous preparations. The above-mentioned Decree supplies the criteria for the evaluation of hazardous preparations, regardless of their intended use, and completes previously undertaken steps, in strict connection with the analogous Directives of the EU, for the problematic complexity of the classification, packaging and labelling of dangerous substances and preparations. The applicative importance of Directive 99/45/EC derives directly from these innovations. Among these, for the first time, the category of "dangerous for the environment" has been extended also to preparations. Moreover, also for the first time, the scope of the Directive is extended to plant protection products and biocides. This paper provides an overview on the results of the hazard classification procedure carried out at national level for plant protection products in light of the new rules and the outcomes in terms of variations of the labels through comparison between previous and new classification. Furthermore the most significant issue which come up during the classification process and the criteria applied for their solution are also reported.